Intra and Inter-Local Item Dependence of Mathematics Items - Opesemowo, Oluwaseyi Aina Gbolade (Research in Social Sciences and Technology- OpenED Network, 2023)
Local Item Dependence (LID) is a desecration of Local Item Independence (LII) which can lead to overestimating or underestimating a candidate’s ability in mathematics items and create validity problems. The study investigated the intra and inter-LID of mathematics items. The study made use of ex-post facto research. The population encompassed all 26,086 Senior Secondary School Students three (SSS 3) in Osun State, Nigeria, and 14,936 SSS 3 students were randomly picked as the sample. National Examinations Council (NECO) mathematics items from June/July 2017 served as the research instrument. The calibrated data were subjected to Yen Q3 statistic. Using a multidimensional three-parameter logistic model, the Yen Q3 statistic is the residual correlation of the items calibrated by Jmetrik software. Results revealed that intra-LID was spotted between Item 8 and Item 7, Item 47 and Item 18, Item 28 and Item 21, Item 47 and Item 29, Item 39 and Item 38, Item 60 and Item 47, Item 52 and Item 51, Item 59 and Item 58 with a Q3 index greater than 0.2 rule of thumb. Similarly, inter-LID revealed bundles 3, 6, 7, 13, and 15 with a Yen Q3 index greater than 0.2. The study concluded that intra and inter-LID was discovered in the NECO mathematics item. It was recommended that NECO should consider intra and inter-LID to ensure more credible questions.